Structure of a Universal Multifunctional Digital Card in the Interest of the Armed Forces of the Republic of Uzbekistan in the Border Area - Rajabovich, Ashurov Furkat (Researchparks Publishing, 2023)
Currently, in digital form, there are topographic and special maps of various scales for most of the territory of the Republic of Uzbekistan, which are morally and technically outdated and does not meet the modern requirements of troops and weapons systems.